Penggunaan Canva sebagai Media Pembelajaran Keterampilan Membaca Bahasa Arab Siswa Kelas X di MAN Kota Batu - Indah Rahmayanti; Abdul Muntaqim Al Anshory; R Taufiqurrochman; Sahrul Muhamad (PALAPA, 2023)
In the digital era, learning activities must be adapted to developments in technology and information. Teachers are required to develop learning media creatively and innovatively. This study aims to determine the use of Canva as a medium for learning Arabic reading skills for class X students at MAN Batu City, student responses to the media and evaluate the use of the advantages and disadvantages. This research approach combines both qualitative and quantitative methods, employing data gathering techniques such as observation, interviews, and questionnaires. The research data respondents were 33 class X MAN Batu City students. The questionnaire instrument uses 13 statements with a Likert scale rating of 1-5 related to the use of Canva as a medium for learning Arabic reading skills for class X IPS 1 MAN Batu City. The results of the study show that using Canva as a media for reading skills is easy to use in learning, both in class and for independent study at home. Student response in using this media is also good. This can be seen from the results of the Pearson correlations for each item above 0.2826. So that the results of the questionnaire from students are valid. The 2-tailed significance of 0.000 <0.05 means that each item is correlated. So it can be concluded that student responses are acceptable. The advantages of using Canva are being able to make learning materials that are visually interesting and the drawbacks are requiring a stable internet network.